¿Tiene cabida en nuestro ordenamiento la objeción institucional para las entidades sanitarias? - Díez Fernández, José Antonio (Anuario de Derecho Eclesiástico del Estado (BOE), 2023)
El debate sobre la nueva ley de eutanasia ha vuelto a poner el foco en el valor que el ordenamiento otorga a la objeción de conciencia de los profesionales de la salud. En este caso, el legislador, no se ha limitado a la regulación individual de este derecho, sino que ha extendido los efectos de la ley a las instituciones sanitarias privadas. En este estudio se trata de argumentar, desde una perspectiva constitucional, si existe o no un anclaje jurídico suficientemente sólido para defender la legalidad de la objeción de conciencia institucional o colectiva
The debate on the new euthanasia law has once again put the focus on the value that the norm gives to the conscientious objection of health professionals. In this case, the legislator has not limited himself to the individual regulation of this right, but has extended the effects of the law to private health institutions. In this study we will try to argue, from a constitutional perspective, whether or not there is a sufficiently solid legal anchor to defend the legality of institutional or collective conscientious objection, based on the jurisprudential recognition of the ownership of fundamental rights –which are not very personal nature– to legal persons. At this point, we consider it very appropriate, for the sake of clarity, to focus the debate not so much on the discussion about whether or not legal entities have a «conscience», but rather on the guarantees that are extracted for the defense of their ideology or institutional purpose of article 16.1 of the Constitution that guarantees ideological freedom and freedom of action to churches and communities. Based on this recognition, it is perfectly feasible to take advantage of the model of the so-called «trend companies» as the most appropriate to guarantee the ideology and guide the practical development of these entities in their relationships both with the Health Administrations and with their users and employees.
Keywords: derechos fundamentales; conciencia; ideario; eutanasia; fundamental rights; conscience; ideology; euthanasia